The Concept Of Taghyir Khalqillah Through Mufassirin Perspective: An Analysis Based On Surah Al-nisa’, Verse 119 - Mohammad Naqib Hamdan; Mohd Anuar Ramli; Mohd Farhan Md Ariffin; Nasiibah Ramli; Nurul Syahadah Mohamad Riza; Hussein 'Azeemi Abdullah Thaidi; Muhamad Firdaus Ab Rahman (Human Resource Management Academic Research Societ, 2024)
Indexed by ERA